Cost of Goods Sold Analysis of Rengginang "Mak Lia" Based on the Full Costing Method - Yulia Variska Putri; Ilviana Variska Putri; Merry Agustin; Cindy Lafylatul Zahro; Rika Maulidah; Mila Dwi Aysah; Siti Nor Kholifa; Nanda Widaninggar (MBA : Journal of Management and Business Aplication, 2024)
This research aims to analyze the determination of basic production prices for Rengginang products based on the Full Costing method, with a focus on the "Mak Lia" as a Micro, Small and Medium Enterprises (MSMEs). The Full Costing method is the main topic of discussion because it is able to provide a comprehensive view of all cost components involved in the production of Rengginang products. This research uses a qualitative approach with case studies as the research method. Data was collected through interviews with business owners, direct observation of the production process, and analysis of documents related to production costs. Historical data on sales, raw material costs, direct labor costs, and fixed overhead costs are also obtained to understand their impact on the cost of goods sold. The research results show that the Full Costing method provides a complete picture regarding all costs incurred by "Mak Lia" in the Rengginang production process, including fixed overhead costs. By using this method, "Mak Lia" can determine the cost of goods sold which includes all costs incurred, including fixed components which are often ignored in other methods.